Value proposition design at training & consulting services company in sharia financial banking Lampung Province at CV. Acceleration Indonesia Juara - Hengki Yuliansyah (Review of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: The study aims to identify the causes of the existing business performance gap and design a Value Proposition Design for Training and Consulting Services Companies in the Sharia Financial Sector in Lampung Province at Cv. Akselerasi Indonesia Juara. Research methodology: The model of this research is exploration research, which is research that begins to observe phenomena and problems occur and to develop initial ideas about them which then move towards refining the research questions. Results: CV Akselerasi Indonesia Juara created a sustainable program to provide training services. Because BPRS likes the service, they don't like it when the service is only limited to the classroom. The ongoing program can be made by providing alumni forums, sharing forums, and even to the ongoing program. Limitation: The company, AKIRA, provides training and consulting services to various institutions and companies, including UKMs, and has three divisions: Public Training, In House Training, and CCC (Coaching, Consulting & Co-management). Contribution: The company has faced challenges in developing its business due to the COVID-19 pandemic, which disrupted the industry of training and consulting services.